Metodyka pracy naukowej w filozofii: Wprowadzenie do warsztatu cyfrowej humanistyki (Księgarnia Akademicka Publishing, 2023)
METHODOLOGIES OF DIGITAL HUMANITIES IN PHILOSOPHY. AN INTRODUCTION The aim of the book is to present the key aspects of research methods in philosophy. Therefore, it is intended primarily for students of philosophy and doctoral students. The authors’ intention is to offer an introduction to independent philosophical work adopting the resources offered by digital humanities, a field which has recently revolutionized the humanities. Digital technologies have significantly changed the ways of working with texts. The introduction of digital tools into philosophy makes it possible to study its broader context and track distant connections between ideas, and significantly facilitates work on source material. The book consists of seven chapters covering the main issues of modern methodology in philosophy. We begin by introducing how to study philosophy, how to find trustworthy texts, and how to benefit from using a library, which is the basic workplace for the humanist. Then we turn to the computer as an important tool of the contemporary philosopher, and discuss topics such as text editing, and the use of search engines for locating Internet resources. The third chapter is devoted to matters related to philosophical writing. We start with ethical issues, and then look at the main types of philosophical works. We also deal with the characteristics of the disseration as a genre. In the fourth part of the book, we discuss the formatting of lists of references and footnotes. The next chapter deals with the art of presenting one’s own research results – in this part of the book we outline the best practices in designing lectures and multimedia presentations. In the last two chapters, which are mainly intended for PhD students. Firstly we address selected issues important for the management of bibliographic data and references in Zotero. Next we discuss the academic activities of a doctoral student, such as publishing academic articles, establishing one’s online academic reputation, important information about the doctoral dissertation, and the stages of the doctoral dissertation assesment process.